Shahab Ahmed and the Hermeneutics of Islam - Milani, Milad (Journal for the academic study of religion, 2020)
In the posthumously published book, What is Islam? The Importance of Being Islamic (2016), Shahab Ahmed (1966-2015) presented a new conceptualisation of Islam to address two points: to re-conceptualise Islam in terms of contradiction, and re-present what it meant to be Islamic as a challenge to existing conceptualisations. This article argues that Ahmed’s rethinking of Islam/Islamic is properly situated as a revivalist catholic hermeneutics, and as such, his conceptualisation is a reworking of insider discourse writ large. It further examines Ahmed’s hermeneutics through a Heideggerian lens.